What drives process preferences? The role of perceived qualities of policymakers and party preferences. - Fernández-Martínez, José Luis; Alarcón-Pérez, Pau; Font-Fábregas, Joan (Springer Nature, 2020)
This article analyzes factors which explain support for the representative model and its two main alternatives: direct democracy and technocracy. It discusses the role played by two understudied explanatory factors: perceptions relating to the personal qualities of the different actors involved in decision-making (i.e. representatives, citizens and experts) and electoral support for mainstream parties (PSOE and PP) and new parties (Ciudadanos and Podemos). We rely on two Spanish surveys from 2011 and 2015. The results show that both perceived qualities and party preferences are linked to support for the three decision-making models. The emergence of new parties in 2015 has reshaped the connection between party choice and process preferences and has made this relationship stronger.
https://openpolicyfinder.jisc.ac.uk/id/publication/8297
Keywords: Democracia directa; Tecnocracia; Process Preferences; Stealth Democracy; Ideology; Political parties